The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/hbm.23244
|View full text |Cite
|
Sign up to set email alerts
|

Brain GABA levels across psychiatric disorders: A systematic literature review and meta‐analysis of 1H‐MRS studies

Abstract: The inhibitory gamma-aminobutyric acid (GABA) system is involved in the etiology of most psychiatric disorders, including schizophrenia, autism spectrum disorder (ASD) and major depressive disorder (MDD). It is therefore not surprising that proton magnetic resonance spectroscopy ((1) H-MRS) is increasingly used to investigate in vivo brain GABA levels. However, integration of the evidence for altered in vivo GABA levels across psychiatric disorders is lacking. We therefore systematically searched the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(209 citation statements)
references
References 116 publications
10
186
3
4
Order By: Relevance
“…In our opinion it would be advisable to include psychiatric comparison groups. Schür et al[100] pointed out that the inhibitory GABA system is thought to be involved in the etiology of several psychiatric disorders. The authors therefore performed a meta-analysis including a total of 40 MRS studies in seven different psychiatric disorders ( n = 1.591).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion it would be advisable to include psychiatric comparison groups. Schür et al[100] pointed out that the inhibitory GABA system is thought to be involved in the etiology of several psychiatric disorders. The authors therefore performed a meta-analysis including a total of 40 MRS studies in seven different psychiatric disorders ( n = 1.591).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased GABAergic inhibition was reported in limbic, frontal, temporal, and respectively insular regions[15,98,99]. Unfortunately, the findings regarding the GABAergic system are partly inconsistent and may not be specific for PD[100]. …”
Section: Discussionmentioning
confidence: 99%
“…Cr is often used as a denominator in signal ratio because Cr is in chemical equilibrium and comparatively unaffected by neurodegenerative processes [68]. GABA levels have also been examined using editing techniques such as MEGA-PRESS that allows for detecting brain GABA independently from other metabolites with overlapping resonances [69]. In most of the 1 H-MRS studies of PTSD, the ACC and temporal lobe structures including the hippocampus, which play an important role in the development and maintenance of PTSD symptoms, were investigated as regions of interest (ROIs) [7071727374].…”
Section: Mrs Studies Of Neurochemical Metabolitesmentioning
confidence: 99%
“…In contrast, GABA levels were lowered in the insula [102], parieto-occipital cortex [96], and medial temporal cortex [96] of patients with PTSD than healthy controls. Although the number of studies was limited, a recent meta-analysis has reported no significant alterations in GABA levels related to PTSD [69]. …”
Section: Mrs Studies Of Neurochemical Metabolitesmentioning
confidence: 99%
“…in vivo GABA rate (3). To the best of our knowledge, no research has been conducted on the immediate response of the human brain, especially in adolescents, after caffeine intake.…”
Section: Introductionmentioning
confidence: 99%